2000
DOI: 10.1116/1.1286396
|View full text |Cite
|
Sign up to set email alerts
|

Fluorocarbon polymer deposition kinetics in a low-pressure, high-density, inductively coupled plasma reactor

Abstract: Maintaining dimensional control and adequate throughput during the etching of submicron features requires plasma etch tools that operate at low pressures and high densities, such as inductively coupled plasmas (ICPs). Unfortunately, in this regime, it has proven difficult to achieve a stable, reproducible chemistry for selective oxide etching of contacts and vias. In particular, it is difficult to control the passivating polymer film which provides etching selectivity to silicon, nitride, and photoresist. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Meanwhile, the polymer deposition was reported to be dominated by the ion-assisted CF 2 deposition. 21 In this experiment, the formation of thicker polymer is clearly supported by the increase in CF 2 from 2.373 a.u. at 10 sccm to 2.706 a.u.…”
Section: A Model Optimizationmentioning
confidence: 75%
“…Meanwhile, the polymer deposition was reported to be dominated by the ion-assisted CF 2 deposition. 21 In this experiment, the formation of thicker polymer is clearly supported by the increase in CF 2 from 2.373 a.u. at 10 sccm to 2.706 a.u.…”
Section: A Model Optimizationmentioning
confidence: 75%
“…This is understandable since in fluorinated plasmas the profile angle is dominated by competing effects between [F]-driven polymer etching and [CF 1 ] or [CF 2 ]-driven polymer deposition [15]. It has been reported that the CF x (x = 1-2) radicals are major precursors to polymer deposition [16].…”
Section: Partial Oes Modelmentioning
confidence: 97%
“…This implies a decrease in the net positive charge in the bulk silicon oxide. It has been reported that CHF 3 produces major precursors to polymer deposition [21]. A thicker polymer is therefore deposited at higher gas ratio, leading to a less charge collection on the Al antenna.…”
Section: Interpretationsmentioning
confidence: 99%